Developmental Dyslexia Across Languages and Writing Systems 2019
DOI: 10.1017/9781108553377.015
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Semantic Processing in Developmental Dyslexia

Abstract: semantic representations. According to this theoretical approach, dyslexics' impairments in phonological decoding lead to reliance on the lexical route. More recent conceptualizations of dual-route models suggest that the use of morphological information speeds lexical access, with both direct and indirect lexical access via letter co-occurrences, such as complex graphemes and morphemes (e.g., TH, CH and RE, ED, respectively;Grainger & Ziegler, 2011). This provides a theoretical context for the speculation tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 82 publications
0
22
0
2
Order By: Relevance
“…Outcomes for our second research question were not straightforward to predict. That is, morphological awareness may be an additional and persistent deficit in students with a self-reported history of reading difficulties, as found for younger students with diagnosed disabilities (Deacon et al, 2016) and in some studies of university students with dyslexia. Alternatively, morphological awareness may be a strength for students with a history of reading difficulties as reported in other studies with university students with dyslexia, helping them to read university material.…”
Section: The Current Studymentioning
confidence: 81%
See 2 more Smart Citations
“…Outcomes for our second research question were not straightforward to predict. That is, morphological awareness may be an additional and persistent deficit in students with a self-reported history of reading difficulties, as found for younger students with diagnosed disabilities (Deacon et al, 2016) and in some studies of university students with dyslexia. Alternatively, morphological awareness may be a strength for students with a history of reading difficulties as reported in other studies with university students with dyslexia, helping them to read university material.…”
Section: The Current Studymentioning
confidence: 81%
“…It has been shown that morphology has a role in skilled word reading (e.g., Crepaldi, Rastle, Coltheart, & Nickels, 2010;Taft, 1994). Furthermore, both developmental research (Deacon, Tong, & Mimeau, 2016) and theoretical models support the notion that individual differences in morphological processing are related to reading achievement (Scarborough, 2001;Stafura & Perfetti, 2017). Consistent with some research on university students with dyslexia (e.g., Cavalli, Duncan, Elbro, El Ahmadi, & Colé, 2017;Law, Wouters, & Ghesquière, 2015;Martin, Frauenfelder, & Cole, 2014), morphological awareness may also be a strength for students with a selfreported history of reading difficulties, acting as a compensation for core deficits in the word reading of these students.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…In alphabetic orthographies, the involvement of morpheme awareness in developmental dyslexia is still under investigation. Broadly, dyslexics tend to show reading-level appropriate morpheme awareness, an argument against morpheme awareness being a causal factor in dyslexic difficulties [ 65 ••]. Where dyslexics do perform poorly in morphemic tasks, this may simply be due to a lack of phonological transparency in the morphological relationships assessed [ 44 ].…”
Section: Morpheme Awarenessmentioning
confidence: 99%
“…It is theorized that when dealing with novel or less automatized words, dyslexics' phonological impairment limits their reliance on the sublexical route that involves decoding prior to lexical access. Thus, individuals with dyslexia are bound to utilize the lexical route, which in a recent reconceptualization of the dual-route model of reading (Grainger & Ziegler, 2011) has been argued to include not only direct lexical access but also indirect access through the aid of complex graphemes and morphemes (Deacon, Tong, & Mimeau, 2016).…”
Section: Ma and Mp In Compensationmentioning
confidence: 99%